A compilation of illicit enrichment legislation and other relevant legislation Annex I of Illicit enrichment: A guide to laws targeting unexplained wealth - Dornbierer, Andrew (Basel Institute on Governance, 2021)
This annex is a compilation of all the relevant legislative instruments located during the research process behind the book Illicit Enrichment: A Guide to Laws Targeting Unexplained Wealth by Andrew Dornbierer, published by the Basel Institute on Governance in June 2021.In line with the definitions contained in Part 1 of the main publication, the laws included in this annex have been categorised as either:- Criminal Illicit Enrichment Laws- Qualified Criminal Illicit Enrichment Laws- Civil Illicit Enrichment Laws- Qualified Civil Illicit Enrichment Laws- Administrative Illicit Enrichment Laws- Other Relevant LawsThe laws are available as an interactive database alongside the main Illicit Enrichment book on Basel LEARN, see illicitenrichment.baselgovernance.org